Clinical characteristics and treatment strategies for A20 haploinsufficiency in Japan: a national epidemiological survey - Shiraki, Mayuka; Kadowaki, Saori; Miwa, Yuki; Nishimura, Kenichi; Maruyama, Yuta; Kishida, Dai; Imagawa, Kazuo; Kobayashi, Chie; Takada, Hidetoshi; Mitsunaga, Kanako; Inoue, Yuzaburo; Ebato, Takasuke; et al. (Frontiers in Immunology, 2025)
BackgroundThe severity of A20 haploinsufficiency (HA20) varies, with no established clinical guidelines for treatment. This study aimed to elucidate the clinical characteristics of, and the efficacy of treatments attempted in, patients with HA20 in Japan.MethodsClinical information on HA20 patients from medical records was retrospectively collected through the attending physicians.ResultsSeventy-two HA20 patients were identified in Japan. And, 54 patients from 37 unrelated families were analyzed in detail. HA20 patients exhibited common features, including recurrent fever, gastrointestinal and musculoskeletal symptoms, and autoimmune disease; various organ disorders (e.g. neurological, liver, and pulmonary diseases) were less common complications. Molecular target drugs (MTDs) were administered in 44.4% of patients, among which anti-tumor necrosis factor (TNF)-α agents showed efficacy in 59.5% of patients. Eleven patients did not experience control of inflammation with initial MTDs, most commonly because of relapse due to secondary failure of MTDs. Anti-drug antibodies were related to the secondary failure of adalimumab in one patient and infusion reactions to infliximab in two patients. In such refractory cases, other treatments (e.g. switching the first MTD to an alternative agent or adding a Janus kinase inhibitor or immunomodulators, or allogeneic hematopoietic cell transplantation [HCT]) were attempted.ConclusionsOur survey revealed that anti-TNF-α agents showed high efficacy. However, secondary failure of MTDs was a significant refractory-related factor in HA20 patients in Japan. Although anti-interferon therapies, thalidomide, and HCT might be potential treatment options, the results of this study suggest that further research is necessary to establish suitable treatments for HA20, especially for those with refractory disease.